2023
DOI: 10.1001/jamadermatol.2023.0391
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Upadacitinib Treatment in Adolescents With Moderate-to-Severe Atopic Dermatitis

Abstract: ImportanceAtopic dermatitis onset usually occurs in childhood. Persistence of disease into adolescence and adulthood is common. It is important to evaluate new treatment options in adolescents because of the high unmet need in this population.ObjectiveTo assess the efficacy and safety of upadacitinib to treat moderate-to-severe atopic dermatitis in adolescents.Design, Setting, and ParticipantsPrespecified analysis of adolescents enrolled in 3 randomized, double-blind, placebo-controlled phase 3 clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A third similar 16-week phase 3 trial ‘AD Up’ that allowed the use of a mid-potency TCS showed similar trend of improvement in atopic dermatitis outcomes [40 ▪▪ ]. The proportion of subjects in the groups placebo/TCS, upadacitinib 15 mg daily/TCS, and upadacitinib 30 mg daily/TCS who achieved the primary and secondary outcomes were: IGA (11 vs. 38 vs. 67%); EASI-75 (30 vs. 63 vs. 84%); NRS-4 itch (21 vs. 46 vs. 52%) (Table 2).…”
Section: Newer Approved Systemic Immunomodulators For Atopic Dermatitismentioning
confidence: 88%
See 1 more Smart Citation
“…A third similar 16-week phase 3 trial ‘AD Up’ that allowed the use of a mid-potency TCS showed similar trend of improvement in atopic dermatitis outcomes [40 ▪▪ ]. The proportion of subjects in the groups placebo/TCS, upadacitinib 15 mg daily/TCS, and upadacitinib 30 mg daily/TCS who achieved the primary and secondary outcomes were: IGA (11 vs. 38 vs. 67%); EASI-75 (30 vs. 63 vs. 84%); NRS-4 itch (21 vs. 46 vs. 52%) (Table 2).…”
Section: Newer Approved Systemic Immunomodulators For Atopic Dermatitismentioning
confidence: 88%
“…Upadacitinib is an oral JAK inhibitor that is FDA-approved for patients 12 years and older with moderate-to-severe atopic dermatitis. It was studied as a monotherapy in two phase 3 identical 16-week double-blind, randomized, placebo-controlled trials, ‘Measure Up 1’ and ‘Measure Up 2’ [40 ▪▪ ]. Three hundred and sixty-eight adolescents, 12–17 years old (weighing ≥40 kg) with moderate-to-severe atopic dermatitis (IGA 3–4) were randomized to three groups: placebo, upadacitinib 15 mg daily, and upadacitinib 30 mg daily.…”
Section: Newer Approved Systemic Immunomodulators For Atopic Dermatitismentioning
confidence: 99%
“…In this article, we reported an analysis of 552 adolescents enrolled in 3 multicenter randomized clinical trials in more than 20 countries to assess the efficacy and safety of upadacitinib to treat moderate-to-severe atopic dermatitis in adolescents. We concluded that “upadacitinib was an effective treatment for adolescents with moderate-to-severe atopic dermatitis, with an acceptable safety profile.” (p526)…”
mentioning
confidence: 99%
“…To the Editor On behalf of my coauthors, I write regarding a previously published article, “Efficacy and Safety of Upadacitinib Treatment in Adolescents With Moderate-to-Severe Atopic Dermatitis: Analysis of the Measure Up 1, Measure Up 2, and AD Up Randomized Clinical Trials,” which was published online first on April 12, 2023, and in the May 2023 issue of JAMA Dermatology . In this article, we reported an analysis of 552 adolescents enrolled in 3 multicenter randomized clinical trials in more than 20 countries to assess the efficacy and safety of upadacitinib to treat moderate-to-severe atopic dermatitis in adolescents.…”
mentioning
confidence: 99%
“…Three randomized clinical trials involving 552 adolescents have demonstrated that upadacitinib administered once daily through 16 weeks make the grade 3 liver enzyme (AST) infrequent (the AST was observed in only 1 patient in the 15-mg treatment group and 1 patient in the 30-mg treatment group). Hence, upadacitinib can be considered to be generally well tolerated and safe in adolescents, similar to that observed in adults [ 11 ].…”
mentioning
confidence: 99%